(untitled) ("Journal "U". Economy. Management. Finance.", 2021)
The income of the population is one of the most important socio-economic indicators, which reflects both the state of the economy and the level of well-being of the population. This article presents the dynamics of various incomes of the population of the Orenburg region for 2017-2019, as well as a comparison with the average per capita income of the population of the Russian Federation. Conclusions are drawn about the importance of the level of income of the population for the economy of the region.